2012
DOI: 10.1007/s12262-012-0757-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Injuries Caused by Penetrating Chest Traumas in Patients Referred to the Emergency Room

Abstract: The aim of the study was to determine the frequency of different injuries caused by penetrating chest traumas, and also the cause and type of trauma and its accompanying injuries. This is a cross-sectional descriptive study, carried out on all patients referred to the emergency room of Shahid Bahonar Hospital, Kerman, from March 2000 to September 2008, due to penetrating chest trauma. The required information including age, sex, cause of trauma, type and site of injury, and accompanying injury was obtained and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The high proportion of assault (23.5%) may not be unconnected with the level of violence and insecurity in the society. Higher figures have been reported in Iran where assault by stab contributed over 90% of chest injuries [33] . The thoraco-abdominal region bears the blunt of penetrating assault due to higher surface area and intention to kill in some cases.…”
Section: Discussionmentioning
confidence: 90%
“…The high proportion of assault (23.5%) may not be unconnected with the level of violence and insecurity in the society. Higher figures have been reported in Iran where assault by stab contributed over 90% of chest injuries [33] . The thoraco-abdominal region bears the blunt of penetrating assault due to higher surface area and intention to kill in some cases.…”
Section: Discussionmentioning
confidence: 90%
“…Penetrating trauma, in this study, was most commonly as a result of gunshot (56.2%) and stab (38.3%) wound. Most international data has reported stab wounds to be more common than gunshot injuries (93.7% vs. 5.94%) [ 3 , 14 ]. In some local studies, stab wounds have been more frequently encountered and in others gunshot wounds [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stabbings account for the majority of penetrating trauma, followed by gunshot wounds (7) (Figure 3). Aghaei Afshar et al reported that stabbing constituted 93.7% of penetrating chest trauma cases, with gunshot wounds making up only 5.94% (7). The clinical presentation of these thoracic injuries depends on the injury's mechanism, the patient's general condition, and the specific anatomical region affected (7,8).…”
Section: General Mechanisms Of Thoracic Injuriesmentioning
confidence: 99%